"Students Who Have the Irish Tongue": The Gaidhealtachd, Education, and State Formation in Covenanted Scotland, 1638–1651. (January 2021) - Cipriano, Salvatore
Abstract: This article examines the Scottish Covenanters' initiatives to revamp educational provision in the Gaidhealtachd, the Gaelic-speaking portions of Scotland, from the beginning of the Scottish Revolution in 1638 to the Cromwellian conquest of Scotland in 1651. Scholars have explored in detail the range of educational schemes pursued by central governments in the seventeenth century to "civilize" the Gaidhealtachd, but few have engaged in an analysis of Covenanting schemes and how they differed from previous endeavors. While the Statutes of Iona are probably the best-known initiative to civilize the Gaidhealtachd and extirpate the Gaelic language, Covenanter schemes both adapted such policies and further innovated in order to serve the needs of a nascent confessional state. In particular, Covenanting schemes represented a unique and pragmatic way to address the Gaidhealtachd's educational deficiencies because they sought practical accommodation of the Gaelic language and preferred the matriculation of Gaelophone scholars into the universities. These measures not only represented a new strategy for integrating the Gaelic periphery into the Scottish state but were also notable for the ways in which they incorporated Gaelophone students into Scotland's higher education orbit—a stark departure from the educational situation in Ireland. By drawing on underutilized manuscript and printed sources, this article examines how the Covenanters refurbished education in the Gaidhealtachd and posits that the Covenanter schemes represented a key facet of the broader process of state formation in 1640s Scotland.